The Implementation of Khuluqiyah Values by Islamic Education Teachers in Preventing Bullying Among Students - Misnahwati Misnahwati; Akrim Akrim; Rizka Harfiani (Dinasti Publisher, 2024)
This research aims to investigate the implementation of Khuluqiyah values by Islamic Religious Education (PAI) teachers in preventing bullying among seventh-grade students at SMP Negeri 2 Perbaungan. As an effort to stop bullying among students, this research focuses on the application of Khuluqiyah values by PAI teachers who seek solutions to the bullying problem in schools. The study employs a qualitative method with a descriptive framework to determine the accuracy and effectiveness of implementing Khuluqiyah values in preventing bullying among students. Data collection techniques include observation, intensive interviews, and documentation. Findings will be strengthened through validity testing and data analysis. The research results reveal that there are three types of bullying behavior at SMP Negeri 2 Perbaungan, including physical, verbal, and relational bullying. These behaviors can occur among some or even all students in the school. The school administration, through PAI teachers, has also implemented Khuluqiyah values as an effort to address this issue. However, there are still challenges that require a lengthy process to achieve optimal results. The school and PAI teachers offer the following solutions: 1) Publishing Standard Operating Procedures (SOP) for handling bullying; 2) Promoting a culture of avoiding intimidation; 3) Encouraging students to feel comfortable sharing their experiences; 4) Helping students become more diligent in worship and drawing closer to Allah; 5) Motivating the community to remain enthusiastic about learning; 6) Enforcing punishments that serve as guidance for perpetrators (such as writing Quranic verses, memorizing short surahs, etc.).